Vaping in pregnancy: a geographically focused assessment of OBGYN provider knowledge regarding the safety and usage of electronic nicotine delivery systems - Madeleine Craig; Anita Tamirisa; Rashmi Madhavan; Ellen Jochum; Ariel Cohen; Dani Zoorob (IMR Press, 2022)
Background: Electronic nicotine delivery systems (ENDS), or vaping, usage has become increasingly popular and generally has a positive perception by the public. However, ENDS are known to contain harmful chemicals and teratogens that induce numerous health consequences to both the pregnant mother and fetus. Despite this, physician knowledge and discussion of ENDS with their pregnant patients remains limited. The main objective of this study was to assess the knowledge of Obstetrics and Gynecology (OBGYN) providers regarding the safety and usage of ENDS in pregnancy. A secondary objective was to understand providers' practices to increase patient education and awareness of the effects of ENDS on pregnant women and developing fetuses. Methods: A 40-question online anonymous survey was developed for this study. The survey aimed at assessing OBGYN providers' understanding of the usage of ENDS and potential harms. The questionnaire was distributed to OBGYN providers in the Midwest and South of the United States of America. Results: One Hundred and four respondents completed the survey (95% response rate). While 96% of providers investigated alcohol and tobacco use during prenatal visits, only 44% routinely inquired about ENDS use. Most providers noted that they had received no formal education about ENDS usage and 55% of providers reported an insufficient understanding of vaping. Conclusions: These results demonstrate that providers lack the education and knowledge about ENDS usage in pregnancy. This is concerning as ENDS usage is rapidly increasing in the United States of America. It is essential to develop educational resources for providers about the risks of vaping and incorporate questions ENDS usage into the social history, especially in pregnancy.